Updating the skating multistage aerobic test and correction for VO2max prediction using a new skating economy index in elite youth ice hockey players - Allisse, M.; Bui, H. T.; Léger, L.; Comtois, A. S.; Leone, M. (The Journal of Strength and Conditioning Research, 2020)
A number of field tests, including the skating multistage aerobic test (SMAT), have been developed to predict VO2max in ice hockey players. The SMAT, like most field tests, assumes that participants who reach a given stage have the same oxygen uptake, which is not usually true. Thus, the objectives of this research are to update the VO2 values during the SMAT using a portable breath-by-breath metabolic analyzer and to propose a simple index of skating economy to improve the prediction of oxygen uptake. Twenty-six elite hockey players (age 15.8 ± 1.3 years) participated in this study. The oxygen uptake was assessed using a portable metabolic analyzer (K4b2) during an on-ice maximal shuttle skate test. To develop an index of skating economy called the skating stride index (SSI), the number of skating strides was compiled for each stage of the test. The SMAT enabled the prediction of the VO2max (ml·kg-1·min-1) from the maximal velocity (m/s) and the SSI (skating strides/kg) using the following regression equation: VO2max = (14.94 × maximal velocity) + (3.68 × SSI) - 24.98 (r = 0.95, SEE = 1.92). This research allowed for the update of the oxygen uptake values of the SMAT and proposed a simple measure of skating efficiency for a more accurate evaluation of VO2max in elite youth hockey players. By comparing the highest and lowest observed SSI scores in our sample, it was noted that the VO2 values can vary by up to 5 ml/kg/min. Our results suggest that skating economy should be included in the prediction of VO2max to improve prediction accuracy.